2011
DOI: 10.1212/wnl.0b013e318212ab1e
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of migraine headaches in severely obese patients after bariatric surgery

Abstract: Severely obese migraineurs experience marked alleviation of headaches after significant weight reduction via bariatric surgery. Future studies are needed to determine whether more modest, behaviorally produced weight losses can effect similar migraine improvements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
69
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(74 citation statements)
references
References 18 publications
5
69
0
Order By: Relevance
“…The result of this study showed that headache frequency was considerably decreased from before to 6 months post-operatively (11.1 vs. 6.7 headache days), with almost half of subjects demonstrating at least a 50 percent discretion (83,84).…”
Section: The Effect Of Bariatric Surgery On Migraine Headachementioning
confidence: 65%
See 2 more Smart Citations
“…The result of this study showed that headache frequency was considerably decreased from before to 6 months post-operatively (11.1 vs. 6.7 headache days), with almost half of subjects demonstrating at least a 50 percent discretion (83,84).…”
Section: The Effect Of Bariatric Surgery On Migraine Headachementioning
confidence: 65%
“…thought, at 6 months after surgery, just 3 (12.5%) of the participants showed this degree of disability. notably, headache improvements occurred post-operatively in spite of that 70% of subjects were still obese, revealing that body weight reduction helps to alleviating headache in the absence of complete improvement of obesity (83).…”
Section: The Effect Of Bariatric Surgery On Migraine Headachementioning
confidence: 97%
See 1 more Smart Citation
“…Given the strong association with obesity and migraine chronification [82], nutrition consultant may improve long-term outcomes, especially given recent evidence that long-term weight loss appears to improve migraine severity [83].…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, metabolic correction accompanied with lifestyle changes would likely enable a significant proportion of migranieurs to achieve a long-lasting migraine relief without heavily seeking preventive therapies that provide temporary symptomatic relief [12] conducted a review of previous studies on childhood migraine and concluded that restoration of ideal body weight of obese children and adolescents would reduce migraine frequency, use of analgesic therapy and risk of progression to chronic migraine. In another study, [13] conducted bariatric surgery on 24 mostly female obese patients who had persistent severe headache as one of the symptom of their obesity related disease. Significant reduction in headache days as well as severity was reported.…”
Section: Migraine and Metabolic Syndromementioning
confidence: 99%